C/Sn deposition on a helical carbon nanofiber matrix as a high performance anode for lithium-ion batteries. (19th April 2022) - Chen, Ge; Jin, Yongzhong; Su, Wei; Li, Yuming; Zhang, Wenjun; Qing, Ting
Abstract : C/Sn/HCNF composites were successfully prepared by solution phase synthesis and carbon thermal reduction. Within the hybrid composite, the HCNFs, Sn and carbon layer show a synergistic effect in improving coulombic efficiency and electrical capacity. Abstract : A simple method for the preparation of carbon/Sn/Helical carbon nanofiber (C/Sn/HCNF) composite by a solution phase synthesis and carbon thermal reduction is introduced, and the composite exhibits good electrochemical performance as an anode for lithium-ion batteries (LIBs). Sn nanoparticles (about 10–15 nm) are grafted onto the surface of HCNFs and coated by a carbon film with a thickness of 10–20 nm. C/Sn/HCNF anode materials can retain a capacity of 610.3 mA h g −1 after 200 cycles at a current density of 200 mA g −1, which is significantly better than 87.2 mA h g −1 by Sn and 241.2 mA h g −1 by Sn/HCNFs at the same rate. The excellent performance and simple preparation method enable the C/Sn/HCNF composite as a potential anode material for LIB application.